Faktor yang Berhubungan dengan Penggunaan Pestisida Kimia dengan Gejala Keracunan pada Kelompok Tani Ngudi Buko Desa Waimital - Ilyas Ibrahim; Maritje S. J. Malisngolar; Ety Dusra; Epi Dusra; Sunik Cahyawati (FORIKES, 2023)
Farmers are a group of workers who are at risk of being exposed to pesticides because activities in agricultural areas always use chemical pesticides to maintain plants. Personal protective equipment is very important when working, especially when spraying pesticides on plants. However, we often find farmers who do not use personal protective equipment when working, so they have the potential to experience pesticide poisoning. The aim of this research was to determine the factors associated with pesticide use and symptoms of pesticide poisoning in the Ngudi Buko farmer group, Waimital Village, Kairatu District. The variables studied were the use of personal protective equipment and the length of time of pesticide spraying as well as symptoms of poisoning in farmers. This type of research was quantitative observational with a cross-sectional design. Probability sampling was used as a research sampling technique, with a sample size of 40 respondents. Research data was collected using questionnaires and field observations. Data analysis was carried out using the Spearman correlation test to see the relationship between variables. The research results showed that the p-value for the use of personal protective equipment factor was 0.03, while for the length of spraying time it was 0.219. It was concluded that the symptoms of pesticide poisoning in farmers in the Ngudi Buko farming group were related to the use of personal protective equipment. If you use personal protective equipment that does not meet the requirements, the risk of pesticide exposure to farmers will be even higher.Keywords: farmer; pesticide; symptoms of poisoning; personal protective equipment ABSTRAK Petani merupakan kelompok pekerja yang berisiko terpapar pestisida karena aktifitas di area pertanian selalu menggunakan pestisida kimia untuk memelihara tanaman. Alat pelidung diri sangat penting dalam bekerja terutama saat melakukan penyemprotan pestisida pada tanaman. Akan tetapi sering kali ditemui petani yang tidak menggunakan alat pelindung diri pada saat bekerja, sehingga berpotensi mengalami keracunan pestisida. Tujuan penelitian ini adalah untuk mengetahui faktor yang berhubungan dengan penggunaan pestisida dengan gejala keracunan pestisida pada kelompok tani Ngudi Buko, Desa Waimital, Kecamatan Kairatu. Variabel yang diteliti yaitu penggunaan alat pelindung diri dan lama waktu penyemprotan pestisida serta gejala keracunan pada petani. Jenis penelitian ini adalah kuantitatif observasional dengan desain cross-sectional. Probability sampling digunakan sebagai teknik pengambilan sampel penelitian, dengan ukuran sampel 40 responden. Pengumpulan data penelitian dilakukan menggunakan kuesioner dan observasi lapangan. Analisis data dilakukan menggunakan uji korelasi Spearmen untuk melihat hubungan antar variabel. Hasil penelitan menunjukkan bahwa nilai p untuk faktor penggunaan alat pelindung diri adalah 0,03, sedangkan untuk lama waktu penyemprotan adalah 0,219. Disimpulkan bahwa gejala keracunan pestisida pada petani di kelompok tani Ngudi Buko berhubungan pemakaian alat pelindung diri. Jika penggunaan alat pelindung diri yang tidak memenuhi syarat maka risiko paparan pestisida pada petani akan semakin tinggi.Kata kunci: petani; pestisida; gejala keracunan; alat pelindung diri